Research into the Experiences of Physical Activity of Female Students, Enrolled in Vocational Education - Gulbinas, Tadas (Jaunųjų mokslininkų darbai, 2015)
The benefit of regular physical activity to physical health has been proven. Regular physical activity guarantees better and longer life, physical and emotional wellbeing, reduces the risk of various diseases. If female students’, enrolled in vocational education, experiences of physical activity in schools remain unknown, it will be difficult to promote physically active lifestyle. The aim of the paper is to analyse female students’ experiences in PE lessons and outside of school hours. Research methods: scientific literature overview, qualitative research, analysis of open-ended survey data. The research findings show that female students’ experiences in PE lessons and outside of school hours are bad. The respondents did not emphasise the benefit of physical health at all. Although scientific literature provides many types of barriers to physical activity; only some of them were identified and were mainly related to time management skills.